Congenital Nephrotic Syndrome: A Case Report - Rahma, Sitti (Universitas Negeri Gorontalo, 2024)
Congenital nephrotic syndrome (CNS) is a rare disorder characterized by massive proteinuria, hypoalbuminemia, hyperlipidemia, and edema that occurs in the first three months of life. The incidence of CNS is about 1.5% of all cases of nephrotic syndrome in children, while the incidence in children is about 2 per 100,000. The pathogenesis of CNS is thought to be due to genetic defects in the components of the glomerular filtration barrier, particularly nephrin and podocin, which cause most similar cases. A perinatal infection may also cause CNS. The most common type of primary CNS is the Finnish type, inherited in an autosomal recessive manner. We report a case of a six-month-old male patient who presented with swelling of the face, abdomen, and genitals since the age of 3 months, which had worsened a week before admission to the hospital. There was no history of nausea, vomiting, fever, or seizures, and the child could drink milk. Physical examination revealed ascites with positive shifting dullness and pretibial, dorsum pedis, and scrotum edema. The liver and spleen were difficult to assess. Laboratory examination revealed leukocytosis (27.8x103/µL), anemia (7.7 g/dL), thrombocytosis (537x103/μL), hypoalbuminemia (1.5 g/dL), dyslipidemia (total cholesterol 374 mg/dL, HDL 7 mg/dL, LDL 69 mg/dL, triglycerides 1196 mg/dL), proteinuria (+3/300), and hematuria (+3/200). A history of urological ultrasound showed right and left nephropathy with mild hydronephrosis and ascites. To sum up, we reported male patient 6 months with congenital nephrotic syndrome. Chromosomal analysis is recommended in this case.